131 Rendering Effects on pet Food Ingredients. (21st September 2022) - Meeker, David L
Abstract: Approximately 31 million tons of animal by-products are generated by livestock and poultry farming, meat processing, and retailing in the U.S. and Canada each year. Utilizing rather than discarding these resources prevents the release of large amounts of GHGs into the atmosphere. Renderers reclaim the carbon from these by-products and transform them into 6.3 million tons of refined animal fats and 8.9 million tons of rendered protein meals for use as animal food ingredients annually. In 2019, 1.5 million tons of rendered protein meals and 289 thousand tons of animal fats were used in pet food, and another 1.83 million tons of fresh and frozen meat and poultry by-products and organ meats were used in pet food without first being rendered. Rendering cookers break down tissues so that fats can be pressed out of muscle, bone, and connective tissues. Rendered products are safe from biological hazards as cooking is done at higher temperatures for longer times than necessary for food safety. The Prioritization of food safety in both rendering and pet food industries in recent years have delayed emphasis on some quality factors. Many citations in literature document that excessive heat damages proteins and decreases their quality and digestibility. Research is planned to provide guidance to renderers on cooking procedures that would meet the needs for processing and food safety without sacrificing quality and digestibility. Other factors that impact the availability and usability of rendered products include parts available for rendering after fresh parts are selected for pet food, upstream human food safety interventions, time and temperature conditions between slaughter and rendering, cooling, drying, storage, transport, and the use of antioxidants, antimicrobials, and other processing aids. Opportunities exist to modernize plants and processes to provide high quality ingredients. Renderers have invested with the pet food sector to collaborate on strategies to improve safety, quality, and sustainability of pet food ingredients.